Uslub Istiārah in the Qur'an According to Tafsir Experts and Its Implications for Balāghah Learning - Abdurahman, Rizki; Rohanda, Rohanda; Atha, Yusuf Ali Shaleh; Sabarudin, Ikbal; Hilmi, Irpan (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
The purpose of this study is to inventory and analyze Qur'anic verses containing uslub istiarah tamtsiliyyah according to exegetes and their implications for balagha learning. The method used in this study is qualitative descriptive with a literature study approach. Primary data sources are obtained from Kitab shafwat al-tafasir and al-tafsir al-Munir. Secondary sources are obtained from articles, books, books that are relevant to the research theme. Data collection techniques are carried out with documentation. While the data analysis technique is carried out by descriptive analysis through stages: (1) collecting and analyzing the verses of istiarah tamtsiliyyah in the Qur'an according to tafisr experts, and (2) describing the implications for learning balaghah. Referring to the results of research based on those obtained in this study that the results of this study show that there are 53 verses of the Qur'an that contain uslub isti'arah tamtsiliyyah in the view of interpreters. The results of this research data have significant implications for efforts to improve and develop balaghah learning materials based on Quranic studies. The problem in this study is limited to the focus of research on Qur'anic verses that contain isti'arah tamtsiliyyah in the Qur'an according to exegetes.